Code of ethics and conduct in the light of corporate governance: the stakeholders’ perspective - Silva, Renato Rodrigues da; Santos, Ruan Carlos dos; Sousa, Antonia Márcia Rodrigues; Orso, Lidinei Éder; Khatib, Saleh Fadel Ahmad (Revista de Administração da UFSM, 2021)
Purpose: To evaluate the theme "Code of Ethics and Conduct" in private or public organizations, considering the relationship between ethical issues and good practices in Corporate Governance, measures that subsidize the planning and strengthening of ethical cultures in the interpersonal context. Design / methodology / approach: The descriptive survey relied on the application of questionnaires and obtained 184 responses from organizations of various types. The study was carried out using codes of conduct made available by companies on their websites, characterized as primary sources. The data collected were worked in the SPSS, tabulated and presented as results in the form of tables or graphs, with appropriate analyses. Findings: The results show the adoption of good practices of integrity, especially on the Code of Ethics and Conduct. The adoption of an ethical code can be considered a way to formalize, encourage and guide responsible behavior among employees and organizations. Seen from the outside, it contributes to creating and maintaining a good corporate reputation and stakeholder trust. In this sense, the reasons behind the creation of a code have been stated in the Shareholders’ Theory, the Legitimacy Theory and the Stakeholder Theory. Originality / value: The Code of Ethics and Conduct arises as an instrument to guide ethical behavior in organizations. Therefore, it is the declaration of the set of rights, duties, business conduct towards stakeholders, reflecting the culture and set of norms that enrich the company’s decision-making processes and guide its behavior.